“Häng med på AI-tåget” Svenska rekryterares användning och upplevelser av AI: En kvalitativ intervjustudie med tematisk analys - Larsson Jönsson,Tess; Stadin,Clara (2026)
The purpose of this study was to examine the usage of Artificial Intelligence in Swedish recruitment as well as gaining a greater understanding of how Swedish recruiters perceive and experience the implementation of Artificial Intelligence in their daily work. The study was conducted as a qualitative interview study using semistructured interviews with nine recruiters that, prior to the data collection, have implemented Artificial Intelligence in their recruitment process. The sample was made through purposive and convenience sampling in order to find participants that met the criteria for the study’s purpose. The data material collected from the interviews were analysed using a thematic analysis. Five main themes emerged from the data including 11 sub-themes. The first research question concerns the nature of use of Artificial Intelligence by Swedish recruiters. Results from the study shows that the usage differs significantly across companies and is being used for several different purposes. Though, the majority of respondents mainly use Artificial Intelligence in the early stages of the recruitment process. The second research question aims to gain a greater understanding of Swedish recruiter’s experience of implementing Artificial Intelligence as a tool in their work. The most prominent results highlighted the recruiter’s positive adjustment towards the implementation of Artificial Intelligence followed by nuanced reflections discussing possible imminences. Furthermore the results suggest a possible knowledge gap regarding the relationship between Artificial Intelligence and discrimination in recruitment.
Keywords: Artificiell intelligens; Rekryteringsprocess; Upplevelser; Rekryterare; Bias; Artificial Intelligence Recruitment process Experiences; Recruiters